2019
DOI: 10.1016/j.clnu.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of the timing of food intake

Abstract: NCT03059576. https://clinicaltrials.gov/ct2/show/NCT03059576.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 56 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…Meule et al (2012) proposed that the biochemical rhythm of appetite-regulating peptides (leptin and ghrelin) might be underlying this behaviour, since the evening chronotype has a more delayed release of ghrelin and leptin than morning chronotypes [30]. The findings from recent research have added to the mounting evidence supporting the connection between chronotype and breakfast [59,60]. A genetic study was conducted among 53 pairs of female twins in order to examine the impact of genetic heritability on meal times [59].…”
Section: Dietary Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Meule et al (2012) proposed that the biochemical rhythm of appetite-regulating peptides (leptin and ghrelin) might be underlying this behaviour, since the evening chronotype has a more delayed release of ghrelin and leptin than morning chronotypes [30]. The findings from recent research have added to the mounting evidence supporting the connection between chronotype and breakfast [59,60]. A genetic study was conducted among 53 pairs of female twins in order to examine the impact of genetic heritability on meal times [59].…”
Section: Dietary Behaviourmentioning
confidence: 99%
“…The findings from recent research have added to the mounting evidence supporting the connection between chronotype and breakfast [59,60]. A genetic study was conducted among 53 pairs of female twins in order to examine the impact of genetic heritability on meal times [59]. They found that the timing of breakfast (56%) and lunch (38%) was mostly influenced by genetic but not dinner time.…”
Section: Dietary Behaviourmentioning
confidence: 99%
“…In humans, genetic influences (heritability) appear to account for a significant proportion. For example, 56% of the variability in food timing, particularly breakfast (32), and 68% of sleep timing on free days (33). An even higher heritability was found in great tits (Parus major), with h 2 of 0.86 ± 0.24 (14).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic component has a greater effect on timing of breakfast. Conversely, the environment is more responsible for timing of lunch or dinner [113]. Excessive adipose tissue in obese individuals has additional health effects.…”
Section: Metabolic Syndrome T2dm and Circadian Rhythm Disordersmentioning
confidence: 99%
“…Nonetheless, advances in the field of circadian disruption treatment are promising. Timing of lunch or dinner is more influenced by environment [113]. The therapeutic interventions may be more effective by modifying factors that take place later on in the day.…”
Section: Conclusion and Possible Treatmentsmentioning
confidence: 99%